Young-onset multiple system atrophy: Clinical and pathological features - Batla, Amit; Balint, Bettina (Movement disorders, 2018)
Background: The onset of multiple system atrophy (MSA) before age 40 years is referred to as “young-onset MSA.” We identified clinical and pathological characteristics that might help with its early diagnosis and distinction from young-onset Parkinson's disease and late-onset MSA. Methods: We reviewed the available clinical and pathological features in cases that fulfilled consensus criteria for diagnosis of probable MSA or had autopsy confirmed MSA with an onset before age 40 years and compared the clinical features with 16 autopsy confirmed cases with young-onset Parkinson's disease and a large published series of late-onset MSA from the European MSA Study Group. Results: We identified 22 patients with young-onset MSA, 8 of whom had available pathology. The mean age of onset was 36.7 years (standard deviation 2.3). Levodopa-induced dyskinesia was more common, whereas myoclonus and pyramidal signs were less common in young-onset Parkinson's disease when compared with young-onset MSA. Dystonia, levodopa responsiveness, levodopa-induced dyskinesia, and pyramidal signs were more common (P < .05) when compared with the data in late-onset MSA. On postmortem analysis, the minimal-change pathological variant was more common in young-onset MSA (n = 2) than late-onset MSA (P = .045), with a mean survival of 11.1 ± 3.2 years (range 5.5-14.6) in pathologically confirmed cases of young-onset MSA. Conclusion: This study has identified useful differences that may improve diagnostic accuracy, help us understand the pathological basis, and assist clinicians with the early diagnosis of young-onset MSA.
Gesehen am 02.03.2020